Acute state of postprandial lipemia induces changes in heart rate variability in healthy adults: clinical pilot study (2016)
PURPOSE: Experimental evidence has shown the relationship between heart rate variability (HRV) and cardiac dysfunction. Nevertheless, it is unknown if changes in HRV can be modified after a high fat meal (HFM) intake. The hypothesis of this study was focused on demonstrating that an acute state of postprandial lipemia induces changes in HRV in healthy adults. METHODS: Prospective interventional study in 14 apparently healthy adults of both sexes, (mean age: 30.71 ± 7.9 years; body weight: 71.53 ± 12.9 kg; BMI 26.2 ± 3.4 kg/m2), with no past medical history of cardiovascular or endocrine disease. The HFM consisted of a breakfast with a total weight of 141g and the following nutritional composition: 31 g fat, 69 g carbohydrate, 31 g protein, and a total of 1171 kcal. Pilot studies confirmed that in a rested state this meal produced a transient impairment in endothelial function. HRV was measured by the mean length of the RR interval (ms), after 10-12h fast (0 min, baseline) and after 60 min, 120 min, 180 min and 240 min postprandial. ANOVA for repeated measures was performed for five times, with Bonferroni correction. RESULTS: The basal value of mean RR was 925.2 ± 48.9 ms. It was identified that postprandial lipemia decreases the HRV in the first 60 min (826.9 ± 31.1 ms) by 10.6% (p< .261 for all ANOVA measures). Nevertheless, it increases at 120 minute by 10% (909.8 ± 49.25 ms) regarding to min 60. This increase was maintained at 180 min (907.6 ± 55.4 ms increment 9.7% compared to min 60). Finally, another decrease was identified at 240 min postprandial (845.7 ± 81.1 ms decrease of 8.6%) regarding to baseline. CONCLUSIONS: This study is the first experimental evidence that demonstrates that a high-fat intake changes HRV in healthy subjects. We recommend further studies with larger sample size in order to complement the results found on this study.